Land management and land-cover change have impacts of similar magnitude on surface temperature - Luyssaert, Sebastiaan; Jammet, Mathilde; Stoy, Paul C.; Estel, Stephan; Pongratz, Julia; Ceschia, Eric; Churkina, Galina; Don, Axel; Erb, KarlHeinz; Ferlicoq, Morgan; Gielen, Bert; Grünwald, Thomas; et al. (Nature climate change, 2014)
The direct effects of land-cover change on surface climate are increasingly well understood, but fewer studies have investigated the consequences of the trend towards more intensive land management practices. Now, research investigating the biophysical effects of temperate land-management changes reveals a net warming effect of similar magnitude to that driven by changing land cover. Anthropogenic changes to land cover (LCC) remain common, but continuing land scarcity promotes the widespread intensification of land management changes (LMC) to better satisfy societal demand for food, fibre, fuel and shelter 1 . The biophysical effects of LCC on surface climate are largely understood 2 , 3 , 4 , 5 , particularly for the boreal 6 and tropical zones 7 , but fewer studies have investigated the biophysical consequences of LMC; that is, anthropogenic modification without a change in land cover type. Harmonized analysis of ground measurements and remote sensing observations of both LCC and LMC revealed that, in the temperate zone, potential surface cooling from increased albedo is typically offset by warming from decreased sensible heat fluxes, with the net effect being a warming of the surface. Temperature changes from LMC and LCC were of the same magnitude, and averaged 2 K at the vegetation surface and were estimated at 1.7 K in the planetary boundary layer. Given the spatial extent of land management (42–58% of the land surface) this calls for increasing the efforts to integrate land management in Earth System Science to better take into account the human impact on the climate 8 .